Helios+ and Helios− Treg subpopulations are phenotypically and functionally distinct and express dissimilar TCR repertoires. Issue 3 (15th January 2019) - Thornton, Angela M.; Lu, Jinghua; Korty, Patricia E.; Kim, Yong Chan; Martens, Craig; Sun, Peter D.; Shevach, Ethan M.
Abstract: The transcription factor Helios is expressed in a large subset of Foxp3 + Tregs. We previously proposed that Helios is a marker of thymic derived Treg (tTreg), while Helios − Treg were induced from Foxp3 − T conventional (Tconv) cells in the periphery (pTreg). To compare the two Treg subpopulations, we generated Helios‐GFP reporter mice and crossed them to Foxp3‐RFP reporter mice. The Helios + Treg population expressed a more activated phenotype, had a slightly higher suppressive capacity in vitro and expressed a more highly demethylated TSDR but were equivalent in their ability to suppress inflammatory bowel disease in vivo. However, Helios + Treg more effectively inhibited the proliferation of activated, autoreactive splenocytes from scurfy mice. When Helios + and Helios − Treg were transferred to lymphoreplete mice, both populations maintained comparable Foxp3 expression, but Foxp3 expression was less stable in Helios − Treg when transferred to lymphopenic mice. Gene expression profiling demonstrated a large number of differentially expressed genes and showed that Helios − Treg expressed certain genes normally expressed in CD4 + Foxp3 − T cells. TCR repertoire analysis indicated very little overlap between Helios + and Helios − Treg. Thus, Helios + and Helios − Treg subpopulations are phenotypically and functionally distinct and express dissimilar TCR repertoires. Abstract : Helios − and Helios + Treg represent two distinct populations and express dissimilar TCR repertoires. Foxp3 expression is stable in Helios + Treg and they effectively suppress autoimmunity. Foxp3 is less stable in Helios − Treg, some convert to effector cells, and they suppress some (IBD), but not all autoreactive (Scurfy) responses in vivo.